2021
DOI: 10.3390/s21041127
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless Self-Excited Vibrational Viscometer with Two Hopf Bifurcations Based on a Piezoelectric Device

Abstract: In this study, we propose a high-sensitivity sensorless viscometer based on a piezoelectric device. Viscosity is an essential parameter frequently used in many fields. The vibration type viscometer based on self-excited oscillation generally requires displacement sensor although they can measure high viscosity without deterioration of sensitivity. The proposed viscometer utilizes the sensorless self-excited oscillation without any detection of the displacement of the cantilever, which uses the interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Furthermore, it was observed that the position of the jumps from low to high frequencies (increasing R 2 ) and from high to low frequencies (decreasing R 2 ) did not match. This defined an hysteresis region delimited by two bifurcations, as also found in [ 27 ].…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, it was observed that the position of the jumps from low to high frequencies (increasing R 2 ) and from high to low frequencies (decreasing R 2 ) did not match. This defined an hysteresis region delimited by two bifurcations, as also found in [ 27 ].…”
Section: Resultssupporting
confidence: 65%
“…Constant values of the potentiometer R 1 ( R 1 = 6.11 kΩ) and polarity ( p = −1 with P = 1) were chosen so that sudden jumps in oscillation frequency were observed when sweeping R 2 [ 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations can be mitigated by inducing the self-oscillation of the resonator in closed-loop feedback platforms, with a better signal-to-noise ratio and quality factor. The problem with these strategies is that they tend to be very non-linear and difficult to model and analyse [ 22 , 23 , 24 , 25 , 26 ]. The use of a Phase-Locked Loop (PLL) to detect low-noise and real-time shifts of frequency caused by changes in the viscosity of the fluid has recently been successfully proposed [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A design problem of a similar qualitative nature is that envisioned in [18] of a network of piezoelectric ultrasonic active sensors embedded throughout a structure and powered by harvested vibrational energy from the structure. In [24], self-excitability and parameter hysteresis are leveraged to develop a vibrational viscometer with improved performance relative to traditional sensor designs relying on frequency-response analysis. Coupling between a physical micro-cantilever and a virtual cantilever simulated by an analog circuit is used in [12] to achieve high-sensitivity mass measurements of tens of nanograms.…”
Section: Introductionmentioning
confidence: 99%